The Political Economy of Apparel Exporting Industrial Parks in Ethiopia - Ali, Mohammed Seid. author. aut Link
XIX, 298 p. 1 illus.
Keywords: This book discusses the maxim of industrialization with a human face or social upgrading, which currently dominates the academic and actual policy discourses, particularly in late-comer economies of the Global South such as Ethiopia. To understand industrialization with social upgrading in the current context of economic globalization, characterized by the Global Value Chain (GVC), the book adopts the Human Rights (HR) perspective to labour relations and employs the Corporate Social Responsibility (CSR) approach to analyze the labour compliance of apparel exporting firms and their respective global brand buyers operating in Ethiopia’s industrial parks. The findings reveal that Ethiopia’s post-2005 state-led industrialization development path, which has firmly embraced strong businessstate alliances, has curbed the power of labour. Further, global brands’ flawed CSR and poor purchasing practices have contributed to the ongoing labour abuses in the country’s industrial parks. If the government does not consciously respond to the “race to the bottom”, the cold current of economic globalization that dominates the global apparel value chain, local industrial workers in Ethiopian industrial parks will continue to face dismal working conditions. Mohammed Seid Ali (PhD) is Associate Professor of Political Economy in the Department of Political Science and International Studies at Bahir Dar University, Ethiopia. He was also a former Presidential Scholar at the African Studies Centre, University of Michigan. .